2019
DOI: 10.37891/kpej.v1i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Item Analysis Using Rasch Model in Semester Final Exam Evaluation Study Subject in Physics Class X TKJ SMK Negeri 2 Manokwari

Abstract: The purpose of this research is to item analyze in semester final exam evaluation using Raschmodel in terms of validity, reliability, and difficulty level study subject in physics class X TKJ SMK Negeri 2Manokwari. This research was a qualitative research that is evaluation of learning outcomes usingquantitative descriptive method with data collection techniques used documentation. The data of respondents44 students with the number of items 30 questions, obtained the result are the validity of the conformity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 1 publication
0
12
0
4
Order By: Relevance
“…Comparison of the percentage of difficulty in this instrument, namely: difficult (25%), moderate (50%), and easy (25%) (table 5). The results of the analysis prove that this test instrument has a good index of difficulty because, overall, the items are relatively easy and easy [16]. 4.…”
Section: Difficulty Indexmentioning
confidence: 86%
“…Comparison of the percentage of difficulty in this instrument, namely: difficult (25%), moderate (50%), and easy (25%) (table 5). The results of the analysis prove that this test instrument has a good index of difficulty because, overall, the items are relatively easy and easy [16]. 4.…”
Section: Difficulty Indexmentioning
confidence: 86%
“…Research on the Rasch model has been widely discussed (Chan et al, 2021;Che Lah et al, 2021;Nielsen et al, 2021;Scoulas et al, 2021;Tseng & Wang, 2021). Previous findings show that the Rasch model can be used by teachers and can be applied in final semester exams in various subjects: Chemistry (Purnamasari & Kartowagiran, 2019), Economics (Alfarisa & Purnama, 2019), Morality (Aqidah-Akhlak) (Pratama, 2020), and Physics (Asriadi & Hadi, 2021;Palimbong et al, 2018). Several similar studies were found, such as investigating the quality of test instruments in measuring students' abilities in exams.…”
Section: Introductionmentioning
confidence: 81%
“…Nilai Person Reliability dan nilai Item Reliability yang merupakan hasil uji reliabilitas item soal. Item yang valid atau dapat diterima harus memenuhi setidaknya dua dari tiga kriteria, diperbaiki jika memenuhi salah satunya, dan dibuang ketika tidak ada yang cocok dengan kriteria ini (Palimbong et al, 2019). Kualitas item soal dari aspek reliabilitas item soal menggunakan nilai Cronbach Alpha jika memenuhi kriteria yang ditunjukkan pada Tabel 1.…”
Section: Analisis Dataunclassified